Multifactorial Diseases Becoming the Epigenetic Factor for the Genz - Manali Patel; Yachna Jha (International Journal of Genetic Modifications and Recombinations, 2024)
This comprehensive paper investigates the complex interplay between multifactorial diseases, particularly obesity and cardiovascular disease (CVD), and their relationship with epigenetic mechanisms, highlighting the transgenerational implications of these interactions. The multifaceted nature of obesity and CVD, involving genetic predisposition, environmental influences, and epigenetic modifications, underscores the intricate pathways contributing to disease susceptibility and progression. Drawing upon a synthesis of diverse research findings, the paper elucidates the critical role of genetic predisposition in shaping disease susceptibility across generations, emphasizing the importance of genetic screening and counseling for identifying at-risk individuals and families. Furthermore, the paper delves into the transgenerational impact of environmental exposures, emphasizing the heritability of epigenetic changes induced by factors such as maternal diet and lifestyle choices. This insight underscores the significance of early-life interventions and maternal health programs in promoting optimal health outcomes for offspring. The recognition of epigenetic programming as a mediator of the long-term effects of early-life exposures highlights the potential for personalized interventions tailored to individual risk profiles, thereby advocating for a proactive and preventive healthcare approach. Overall, this paper provides valuable insights into the complex interplay between multifactorial diseases, epigenetic mechanisms, and their transgenerational implications, emphasizing the significance of adopting a holistic approach to address the burden of obesity and CVD across generations. It underscores the importance of implementing targeted interventions and policies aimed at promoting long-term health and well-being for future generations, thereby advocating for a proactive and preventive paradigm in public health initiatives. Comprehending the transgenerational effects of multifactorial diseases, particularly considering epigenetic influences, is of utmost importance in shaping future health outcomes and devising focused interventions aimed at reducing the risk of obesity and cardiovascular disease across broader demographics.
Keywords: Cardiovascular disease (CVD); Epigenetic mechanisms; Multifactorial diseases; Transgenerational implications; obesity